Health-related quality of life and participation after inpatient rehabilitation of sepsis survivors with severe sequelae: a cohort study - Ulf Bodechtel; Thea Koch; Lars Heubner; Peter Spieth; Ines Rößler; Jan Mehrholz (Medical Journals Sweden, 2024)
Objective: To describe health-related quality of life and participation after rehabilitation of severely affected sepsis survivors. Design: Cohort study. Subjects/Patients: Patients with severe sequelae after sepsis treated in a multidisciplinary rehabilitation pathway were included. Methods: Patient characteristics at the time of diagnosis, and the outcome 3 months after discharge from rehabilitation are described. At that time, health-related quality of life, social participation, and the rate of living at home were measured. Results: Of the 498 patients enrolled, 100 severely impaired patients were transferred for a multidisciplinary rehabilitation approach. Fifty-five of them were followed up at 3 months. Descriptive and inference statistics showed that 69% were living at home with or without care. Health-related quality of life and participation scores were 0.64 ± 0.32 for the EQ-5D utility index and 54.98 ± 24.97 for the Reintegration of Normal Living Index. A multivariate regression model explaining health-related quality of life at 3 months included age, lower limb strength, and walking ability during rehabilitation (r2 = 0.5511). Participation at 3 months was explained by age, body mass index, lower limb strength, and duration of tracheal intubation (r2 = 0.6229). Conclusion: Patients who have experienced serious sepsis with severe sequelae can achieve a moderate level of quality of life and participation within a multidisciplinary pathway.